A giant vesical calculus - Rahman, M; Uddin, A; Das, GC; Akanda, NI (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S57-59 The abstract of this article is available on the PubMed website